Effect of Variations in Water Addition On Maximum Dry Weight in Clay Soil Compaction - Rina Dwi Fatika; Agata Iwan Candra; Mahardi Kamalika Khusna Ali (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
Soil is a crucial element in construction, serving as the foundation for structural support. Soil compaction is one of the primary methods to enhance soil stability, especially for clay soil, which expands and shrinks due to changes in moisture content. This study aims to analyze the effect of water content variation on the maximum dry unit weight in clay soil compaction. The experimental testing was conducted in the Civil Engineering Laboratory of Kadiri University using the TS-365 Automatic Standard Proctor machine. The water content variations used were 15%, 18%, 20%, 23%, and 26%. The results showed that the optimum moisture content for achieving the maximum dry unit weight was 23%, with a maximum dry unit weight of 1,743 g/cm³. Increasing water content up to the optimum point increases soil density, but excess water reduces the dry unit weight due to particle separation. This research contributes to optimizes clay soil compaction for more stable and sustainable construction. By determining the optimum moisture content, the compaction process can be conducted more efficiently, minimizing the risk of soil volume changes and improving soil-bearing capacity for long-term infrastructure development.